Chemosensory control by commissural nucleus of the solitary tract in rats - Favero, Michele T. [UNESP]; Takakura, Ana C.; de Paula, Patricia M. [UNESP]; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP]; Moreira, Thiago S. (Elsevier B.V., 2011)
The commissural nucleus of the solitary tract (commNTS) is a main area that receives afferent signals involved in the cardiovascular and respiratory control like those related to chemoreceptor activation. however, the importance of the commNTS for the cardiorespiratory responses to chemoreceptor activation is still controversial. In the present study, we investigated the cardiorespiratory responses to hypoxia or hypercapnia in anesthetized and conscious rats treated with injections of the GABA-A agonist muscimol into the caudal portion of the commNTS. Male :Holtzman rats (280-300g) were used. In conscious rats that had a stainless steel cannula previously implanted into the commNTS, the injection of muscimol (2 mM) into the commNTS reduced the pressor response (16 +/- 2 mmHg, vs. saline: 36 +/- 3 mmHg) and the increase in ventilation (250 +/- 17 ml/min/kg, vs. saline: 641 +/- 28 ml/min/kg) produced by hypoxia (8-10% O(2)). In urethane anesthetized rats, the injection of muscimol into the commNTS eliminated the pressor response (5 +/- 2 mmHg, vs. saline: 26 +/- 5 mmHg) and the increase in phrenic nerve discharge (PND) (20 +/- 6%, vs. saline: 149 +/- 15%) and reduced the increase in splanchnic sympathetic nerve discharge (sSND) (93 +/- 15%, vs. saline: 283 +/- 19% of baseline) produced by hypoxia. However, muscimol injected into the commNTS did not change hypercapnia (8-10% CO(2)) induced pressor response or the increase in the sSND or PND in urethane anesthetized rats or the increase in ventilation in conscious rats. The present results suggest that the cardiorespiratory responses to hypoxia are strongly dependent on the caudal portion of the commNTS, however, this area is not involved in the responses to hypercapnia. Crown Copyright (C) 2011 Published by Elsevier B.V. All rights reserved.
Keywords: Central and peripheral chemoreflex; Breathing; Sympathetic activity; NTS; Hypoxia